Childhood cognitive ability and the use of long-term care in later life - Iveson, Matthew; Altschul, Drew; Deary, Ian (International Journal of Population Data Science, 2019)
Background As the population ages the demand for care is predicted to increase. Previous studies have reported that individuals with poorer post-morbid cognitive ability are at higher risk of entering long-term care, both institutionalised care and home-based care. Given that post-morbid cognitive ability is sensitive to the type and severity of morbidity, it remains unclear whether higher cognitive ability, as a trait-level measure of individual differences, contributes to care usage. Some success has been observed using non-cognitive early-life circumstances such as socioeconomic circumstances as pre-morbid predictors of care risk. However, the contribution of early-life cognitive ability has yet to be examined. Main Aim We investigate the association between early-life circumstances, particularly cognitive ability, and the risk of entry into long-term care in later life (age 65+). Methods Veterans were identified using the South London and Maudsley Biomedical Research Centre (SLaM) case register – a database holding secondary mental health care electronic records for the South London and Maudsley National Health Service Trust of 300,000 patients. We developed two methods. An NLP and machine learning tool were developed to automatically evaluate personal history statements written by clinicians. Results This study uses a large sample of individuals born in Scotland in 1936 and who took part in the Scottish Mental Survey 1947. It links research data from childhood to routinely-collected administrative and healthcare records from across the life course. Conclusion We demonstrate the importance of early-life factors for predicting care usage in later life and how this role differs between types of long-term care. The implications of the results for research and policy will be discussed.